Analysis of Potential Site for Managed Aquifer Recharge Scheme in the Upper Greater Mae Klong Irrigation Project, Thailand - Yutthana Phankamolsil (2022)
This study developed a groundwater flow model to propose the possible Managed Aquifer Recharge (MAR) scheme for sustainable use of groundwater in the Upper Greater Mae Klong Irrigation Project, Thailand. The site suitability for MAR scheme was assessed through the GIS– based Multi–Criteria Decision Making (MCDM) using the Simple Additive Weighted (SAW) method. Five key relevant factors namely; groundwater drawdown, soil texture, depth to groundwater table, land slope and distance to surface water source were chosen as assessment criteria and reclassified for the analysis of site selection for MAR scheme. The results illustrate the potential site for the managed aquifer recharge scheme in the southwest of the Phanom Thuan Operation and Maintenance Project where soil texture is immensely sandy loam. The results of groundwater flow model also exhibit that 14 designated injection wells with discharge rate of 200 m3 d-1, each of which delineated in the potential area, can increase the hydraulic head in the aquifer ranging from 0.00–0.50 m during 2000–2016. In addition, a high increase of the hydraulic head in the aquifer is found nearby the locations of designated injection wells.